Outcomes of patients treated with minimally invasive plate osteosynthesis in the management of distal tibial fractures - Randhawa, Prateek Singh; Joshi, Gururaj; Mankar, Pratik Ajay (International Journal of Research in Orthopaedics, 2023)
Background: Distal tibial fractures are a common injury, often caused by high-energy trauma, and can result in significant morbidity. Traditional surgical management with open reduction internal fixation (ORIF) is associated with complications including infection and soft tissue injury. Minimally invasive plate osteosynthesis (MIPO) has emerged as a potential alternative, with advantages including less soft tissue injury and a faster return to function. The study aimed to evaluate the outcomes of MIPO for distal tibial fractures. Method: Sample size of 38 patients between 18-80 years of age with distal tibial fractures treated with MIPO was included. Patient demographics, fracture characteristics, surgical details and postop outcomes collected. Results: A total of 38 patients with distal tibia fractures with a mean age of 44.36 years were included in the study. The mean duration of hospital stay was 12.71 days, and the time required for a union was 18.61 weeks. The AOFAS score improved significantly from 3 to 6 months after surgery. However, 15 patients (34.88%) reported complications, with deep infection and skin necrosis being the most common. Out of 43 patients, 11 underwent culture and sensitivity testing, with no growth in 5 cases, and the remaining cases showed various bacterial infections. Seven patients underwent implant removal due to complications. Conclusions: The study provides valuable information about the use of MIPO in treating distal tibia fractures, as well as the risk of complications associated with this approach.